Sustainability Reporting: Sebuah Analisis Bibliometrik Pada Database Scopus - Ajeng Tita Nawangsari; Mochammad Ilyas Junjunan; Resha Dwi Ayu Pangesti Mulyono (Pusat P2M Politeknik Negeri Batam, 2020)
The aims of this study is to capture the development of sustainability reporting research using the Scopus Database. This study use bibliometric method to present quantitative result in capturing those development. There are several indicators used such as citation numbers, authorship, source of the articles, theory mapping, research approaches and country. The result show that the highest citation number for sustainability reporting were 861. The most research approach used is qualitative and the commonly used theories in the field of sustainability reporting is legitimacy and stakeholders theory. García-Sánchez I.M was the most productive author in publishing sustainability reporting research with 12 total number of publication. Based on the article source journal of cleaner production was the most leading journal in sustainability reporting research with 76 publications on it. Based on the country, USA has the highest number of sustainability reporting publication than many other countries.